Comparison of accelerograms and response spectra in media: soil and rock, Boyacá, Colombia (2021)
Vibration control involves the measurement of these disturbances in a production blasting. If the registered level of vibrations is less than the criterion of prevention, the operating load may be progressively increased until the vibration intensities were equal to the maximum allowable value. In this sense, the analyses in this article serves as preliminary studies to establish a standard table of maximum load for delay times in relation to the distance to the structures to protect, speed and/or acceleration of the particle.